How Do Governments Respond to Food Price Spikes? Lessons from the Past - Anderson, Kym; Nelgen, Signe (2012)
Food prices in international markets spiked upward in 2008, doubling or more in a matter of months. Evidence is still being compiled on policy responses over the following two years, but lessons can be learned from the price spike in 1973, the magnitude and speed of which were similar to those experienced around the 2008 spike. In developing countries, policy responses to the earlier spike lowered the (negative) nominal assistance coefficient for agriculture by one-third between 1972 and 1974 before it was returned to the same level by 1976. That was twice the extent of the fall and recovery of the (positive) nominal assistance coefficient for high-income countries. However, the trade and welfare effects of those changes were much less for developing than high-income countries, suggesting the dispersion of distortion rates among farm industries decreased in developing countries. The adjustments were virtually all due to suspension and then reinstatement of import restrictions, with changes in export taxation by developing countries playing an additional (but minor) role during 1972-74. This beggar-thy-neighbor dimension of each government s food policies is worrying because it reduces the role that trade between nations can play in bringing stability to the world s food markets. More effort appears to be needed before a multilateral agreement to desist can be reached.